Using experimental methods in environmental and resource economics - List, John A., 1968-; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar, 2006)
This book explores frontier work at the intersection of experimental and environmental economics, with cutting edge research provided by premier scholars in the field. The book begins by focusing on improving benefit-cost analysis, which remains the hallmark of public policy decision-making around the globe. The contributors provide innovative avenues to credibly lead to more efficient policies.
1. Anchoring and yea-saying with private goods : an experiment / Ian Bateman ... [et al.] -- 2. Market price endogeneity and accuracy of value elicitation mechanisms / Jayson L. Lusk and Matthew Rousu -- 3. Hypothetical bias over uncertain outcomes / Glenn W. Harrison -- 4. The use of a real-money experiment in a stated-preference survey / John Horowitz -- 5. Mechanisms for addressing third-party impacts resulting from voluntary water transfers / James J. Murphy ... [et al.] -- 6. Peer enforcement in CPR experiments : the relative effectiveness of sanctions and transfer rewards, and the role of behavioural types / Daan van Soest and Jana Vyrastekova -- 7. Experimental approaches to understanding inter-cultural conflict over resources / Paul J. Ferraro and Ronald G. Cummings -- 8. Behavioural economics and the valuation of non-marketed goods and services : the lab, the behavioural anomalies and the policy-maker / Wiktor Adamowicz, Jonathan E. Alevy and John A. List.
Includes bibliographical references and index.
Keywords: Environmental economics -- Methodology; Natural resources -- Management -- Methodology; Electronic books